Des pratiques funéraires marginales entre les VIe et IIIe millénaires Av. J.-C. en Europe tempérée ? Le cas des ossements humains en contexte non sépulcral - Jean-Gabriel Pariat (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Burials are particularly visible evidence of the funerary practices within a group, but are not necessarily the most representative trace of these practices. Over the last thirty years, the many human remains discovered outside burial contexts have led us to consider different methods of funerary practices for the period between the 6th and 3rd millennia B.C. in temperate Europe. Are the remains present in the final burial site the result of deliberate handling, or rather do they come to be there because of accidental circumstances independent of human control? Does the phenomenon of human remains outside burial contexts represent a unique reality in time? Our approach takes into account techniques developed in anthropological field work in relation to these contexts. It calls on the elaboration of a solid analysis grid for examining the sites systematically with the same approach. Through the results obtained we define the criterion of inspection intended to determine the conditions of the human remains on arrival at the final burial site. Finally, we are also attempting to discover the possible development of these customs in terms of time and space.